Determinants of revenue management practices and their impacts on the financial performance of hotels in Kenya: A proposed theoretical framework - Michael Murimi; Billy Wadongo; Tom Olielo (Future Business Journal, 2021)
This conceptual paper aims at identifying a theoretical framework for the determinants of revenue management (RM) practices and their impacts on the financial performance of hotels. To create this framework, a two-phased process is employed where the first stage involves an explicit examination of the literature related to practices of revenue management and their determinants and to hotel financial performance. The second stage involves an enhancement of the framework. The theoretical structure is developed based on past theoretical explanations, and empirical analysis is conducted in the fields of revenue management. The researchers propose a theoretical framework illustrating how revenue management practices and their determinants affect the financial performance of Kenyan hotels. The use of contingency theory and its justifications and inadequacies among studies on revenue management in hotels is highlighted. The methods highlighted by the reviewed theoretical framework may be utilized to organize revenue management (RM) practices and their determinants for Kenyan hotels. Measurements for the financial performance of hotels are also described. Last, the researchers call for empirical research that authenticates the proposed model using a cross-sectional survey. The present work can inspire scholars and specialists to determine how RM practices and their determinants impact the financial performance of hotels. By assimilating knowledge from numerous disciplines, this paper emphasizes aggregated awareness surrounding the conceptualization of RM, RM practices adopted in hotels, and the financial performance of hotels.
Keywords: 650; Contingency theory; Determinants; Determinants of the revenue management framework; Financial performance of Kenyan hotels; Hotels in Kenya; Revenue management; Revenue management practices